2011
DOI: 10.1680/geolett.11.00032
|View full text |Cite
|
Sign up to set email alerts
|

Compression and shear wave propagation in cemented-sand specimens

Abstract: Ultrasonic and bender element tests in the laboratory are typically used to measure elastic modulus and damping ratio. However, interpretation of the results is challenging for a variety of reasons, including the influence of experimental details, geometrical effects and the analytical techniques used for data processing. It is therefore convenient to cross-check results by performing several independent measurements. Three different types of measurements were performed on cementedsand specimens. Longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This index was first presented by Consoli et al (2007) to analyze unconfined compression tests, later proving to be quite adequate to represent small strain stiffness (e.g., Consoli et al 2009;Amaral et al 2011a) from seismic wave measurements as included in this paper.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This index was first presented by Consoli et al (2007) to analyze unconfined compression tests, later proving to be quite adequate to represent small strain stiffness (e.g., Consoli et al 2009;Amaral et al 2011a) from seismic wave measurements as included in this paper.…”
Section: Resultsmentioning
confidence: 97%
“…In geotechnical engineering, several authors (e.g., Viggiani and Atkinson 1995;Brignoli et al 1996;Greening and Nash 2004;Leong et al 2005;Arroyo et al 2006;Alvarado and Coop 2012) have reported difficulties in signal interpretation for soil dynamics purposes, using bender elements (BE) tests. On the other hand, other authors (e.g., Khan et al 2006Khan et al , 2011Tallavó et al 2009Tallavó et al , 2011Amaral et al 2011a) have implemented signal transformation techniques to evaluate soil dynamic properties using piston-type ultrasonic transducers. In any case, most of these works report the effect of the subjective interpretation on the obtained results, and, therefore, the operator experience has an important role in these analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a well characterized soil and extensive geotechnical data has been gathered both for the parent soil alone [20] and for its mixtures with cement ( [21], [22], [23] and [24]). …”
Section: Compacted Cemented Silty Sandmentioning
confidence: 99%
“…Since the used cement is a rapid curing agent, no significant differences were observed in the results obtained in the specimens tested at 28 days of curing and after this period (Amaral et al, 2011). V P and V S values are presented in Table 4 as well as the elastic moduli computed from these values (M 0 , E 0 , G 0 , and m 0 ).…”
Section: Dynamic Testsmentioning
confidence: 99%